DIVERSIFIKASI PENDAPATAN DALAM USAHA PETERNAKAN AYAM PETELUR DI UD MEGA PUTIH LIMBOTO - Fadiilah Zalzabillah Lihawa; Supriyo Imran; Yuriko Boekoesoe (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The research aimed to (1) determine the production process in layer chicken farming at UD Mega Putih and (2) determine the diversification of profits and feasibility of layer chicken farming at UD Mega Putih. This research used descriptive research in the form of a case study. The informants involved in this research were employees at UD Mega Putih, where primary data and secondary data were used in research activities. The data were collected through in-depth interviews and observation while the data analysis was carried out using income analysis, business feasibility, and break-even point. The analysis included cage depreciation cost, equipment depreciation cost, tax cost, seed cost, feed cost, medicine cost, electricity cost, labor cost, and marketing cost in one cycle, namely 2 years (730 days) by calculating based on the results field observation, namely interviewing respondent (Owner of UD Mega Putih). The research findings indicated that the UD Mega Putih layer chicken farming business earned an income of IDR 7,888,166,667/ cycle (730 days) for layer chicken with several 9,500 chickens, IDR 70,000,000/ cycle (60 days) for pullets with several 1000 chickens, and IDR 990,000/ cycle (60 days) for 90 sacks of manure. Thus, the income earned from the layer hen farming business at UD Mega Putih was feasible and profitable.